PERILAKU SEKSUAL REMAJA DI KELURAHAN PURUS KECAMATAN PADANG BARAT - Fitri, Fransiska Tenisa (Pendidikan Sosiologi, 2014)
The background of this research because of the teen couples who make sexual behavior such as cafes tent shaped umbrellas are located in the Village area Purus. Where the conditions of these umbrellas are very low and can be set so that the teen couple easily perform sexual behavior in the cafe. Sexual behavior that they do from holding hands, kissing up to making out (petting) The purpose of this study is to see 1) Forms of sexual behavior in the cafes do tent shaped umbrellas are located in the Village Purus Western District of Padang 2). Motif teens doing sexual behavior in the cafes shaped umbrellas are located in the Village Purus Western District of Padang The theory used is a theory developed by Alfred Phenomenology Shcutz. According to Alfred Schutz human action is determined by the meaning that is understood about something called the motif . Where they have reason to perform certain actions. Alfred Schtuz divide motives that influence human action into two parts: 1.) Because motive, which means the motivation that grows through experience and the individual as a member community. In order motive, the means and the motivation that comes from seeing growing presence values of the range of action now for the future. (Craib, 1986. 143) This research approach is qualitative descriptive type of research to develop the problem under study, and subjects taken Purposive Sampling totaling 14 informants study. The technique of collecting data through observation, interviews, document study. Data analysis techniques: 1). Data collection, 2). Data reduction, 3). Presentation of data, 4). Conclusion. Location of the study was conducted in the Village Purus Western District of Padang Padang. Based on the results obtained the following conclusions: 1 Shape of sexual behavior carried out by a pair of teenagers: a) In contact (touching), b) Kissing c) petting. 2 Motif teens doing sexual behavior in the cafe tent shaped umbrellas are located in the Village of Purus. a) Availability of facilities, b) Affordable Price c) Place Romance, d) Closed & Dark.